Preventive Lifestyle Interventions for Non-Communicable Diseases: Community-Based Innovations - Miftahul Jannah; Chen Mei; Asriana Abdullah; Yang Xiang (Yayasan Adra Karima Hubbi, 2025)
Non communicable diseases (NCDs) remain a leading global health challenge, disproportionately affecting low- and middle-income countries and placing substantial burdens on healthcare systems and communities. Increasing evidence shows that preventive lifestyle interventions embedded in community settings can mitigate behavioral risk factors, yet empirical analyses of innovative community-based models remain limited. This study aims to examine the effectiveness of community-driven preventive lifestyle interventions in reducing modifiable NCD risk indicators and strengthening local health resilience. A mixed-methods design was employed, integrating quantitative assessment of biometric and behavioral indicators with qualitative exploration of community participation, program acceptability, and perceived benefits. Findings demonstrate that structured community interventions such as peer-led education, culturally adapted physical activity programs, and neighborhood health monitoring resulted in significant improvements in dietary behavior, physical activity levels, and blood pressure profiles across participating groups. The study concludes that community-based innovations play a critical role in promoting sustainable lifestyle modification and offer scalable models for NCD prevention, particularly in resource-constrained settings.